2021
DOI: 10.1002/mrd.23518
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a gel culture system made of polysaccharides (xanthan gum and locust bean gum) on in vitro bovine oocyte development and gene expression of the granulosa cells

Abstract: Xanthan gum (XG) and locust bean gum (LBG) are nontoxic polysaccharides that produce culture substrates. The present study examined the effect of XG-LBG gel on in vitro bovine oocyte growth and gene expression in granulosa cells. Oocytes and granulosa cell complexes (OGCs) were cultured in vitro on plastic culture plate (Plate) or XG-LBG gel for 16 days. OGCs formed a dome-like cavity surrounding the oocytes on plate but formed a spherical follicle structure on XG-LBG gel. The total granulosa cell numbers of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The XG-LGB gel had abundant hydroxyl oxide-bound residues and was negatively charged, with soft and low adhesive character to the cellular membrane; consecutively, granulosa cells cultured on the gel did not attach to the gel substrate and formed a spheroid cell mass [ 6 ]. In general, cells proliferate on a stiff substrate through focal adhesion activation and ECM–cell interactions, and this conventional notion cannot explain our findings that cumulus cells and oocytes cultured on soft and less adhesive XG-LGB gel promoted focal adhesion and ECM receptor interactions in both cells and oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The XG-LGB gel had abundant hydroxyl oxide-bound residues and was negatively charged, with soft and low adhesive character to the cellular membrane; consecutively, granulosa cells cultured on the gel did not attach to the gel substrate and formed a spheroid cell mass [ 6 ]. In general, cells proliferate on a stiff substrate through focal adhesion activation and ECM–cell interactions, and this conventional notion cannot explain our findings that cumulus cells and oocytes cultured on soft and less adhesive XG-LGB gel promoted focal adhesion and ECM receptor interactions in both cells and oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, PI3K signaling was a top enriched pathway associated with the DEGs in cumulus cells; however, whether the same mechanism works in gel–cell interaction remains unclear. Our previous report showed that embryos cultured on the XG-LGB gel upregulated actin formation and cadherin localization [ 5 ], and oocyte granulosa cell complexes derived from early antral follicles cultured on the XG-LGB gel upregulated genes associated with focal adhesion and ECM interactions [ 6 ]. Gel substrate then transfers certain signals to activate focal adhesion and ECM interaction-related molecules on cumulus cells and oocytes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several aspects of the efforts employed to improve culture systems, and these include the preparation of ovarian tissues [18], isolation of follicles and oocytes [19,20], design of culture plates [21][22][23], creation of a matrix for media [24][25][26], and inclusion of supplements into media [27]. Additionally, the study of in vivo follicular development [28] and related signaling pathways [29,30] can be the best means of achieving reconstitution of the follicular environment in living animals.…”
mentioning
confidence: 99%